Politik Hukum Pemerintah Indonesia Bidang Lingkungan Hidup Pasca Berlakunya Undang-Undang Nomor 6 Tahun 2023 Tentang Penetapan Peraturan Pemerintah Pengganti Undang-Undang Nomor 2 Tahun 2022 Tentang Cipta Kerja Menjadi Undang-Undang - Sihotang, Nurleli; Leviza, Jelly; Akbar Nasution, Faisal; Afnila (LPPM Universitas Ekasakti Padang, 2024)
The Indonesian government's legal policy in the environmental sector has been regulated in Article 28H paragraph (1) and Article 33 paragraph (4) of the 1945 Constitution of the Republic of Indonesia, namely regarding the right to a good and healthy environment as a human right and the implementation of the national economy based on the principles of sustainable and environmentally sound development. To increase investment and make it easier to obtain environmental approval, the Government made changes to regulations regarding the environment which were previously regulated by Law Number 32 of 2009 concerning Environmental Protection and Management. The problems discussed in this study are how the shift in legal politics in the environmental sector after the enactment of Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation into Law, how changes in environmental regulations after the enactment of Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation into Law, how is the settlement of environmental disputes through filing an administrative lawsuit at the State Administrative Court after the enactment of Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation into Law. This research uses normative legal research methods by examining library materials and the type of research used in this research is an inventory of positive law. The results of this study indicate that the government's legal politics in the environmental sector has shifted after the enactment of Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law because of the ease of obtaining environmental approval and increasing investment, not in accordance with the legal politics of environmental management and protection stipulated in Article 28 H paragraph (1) and Article 33 paragraph (4) of the 1945 Constitution of the Republic of Indonesia and the environmental development agenda which is a national priority agenda in the 2020-2024 National Medium-Term Development Plan.The ease of obtaining environmental approval can be seen from the loss of public participation in the AMDAL document, the change of environmental permits to environmental approval, the withdrawal of the authority of the Regional Government to the authority of the Central Government, the revocation of the provisions of the article regarding absolute liability without the need to prove the element of fault (stict liability), the revocation of the provisions of the article regarding the cancellation of environmental permits through court decisions, the revocation of the provisions of the article regarding the right to administrative lawsuits in environmental disputes in the State Administrative Court, and the change of articles regarding environmental crimes from formal crimes to material crimes. The settlement of environmental disputes through administrative lawsuits at the State Administrative Court after the enactment of Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation into Law is Individuals, business entities incorporated or not incorporated, and / or Environmental Organizations whose interests have been and / or have the potential to be harmed by State Administrative Decisions and / or Government Administrative Actions can file a lawsuit at the State Administrative Court with the legal basis of the Supreme Court of the Republic of Indonesia Regulation Number 1 of 2023 concerning Guidelines for Adjudicating Environmental Cases.